The Use of Biofilmed Biofertilizer to Improve Soil Chemical Fertility and Yield of Upland Kangkung (Ipomoea reptans) on Vertisol - Sudadi Sudadi; Ega Yuana Putri; Suntoro Suntoro (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2020)
The application of biofilm biofertilizer is potential to improve soil fertility and increase plant yield. The research aimed to assess the use of organic fertilizer decomposed with biofilm biofertilizer to improve soil fertility and yield of upland kale in Vertisol. The field experiment was conducted in Vertisol at Jaten, Karanganyar, Central Java, arranged in a Randomized Complete Block Design with a single factor, which was organic fertilizer dose consisting of 0, 3, 6, 9, 12, 15, 18, and 21 ton.ha-1 organic with NPK fertilizer as comparison treatment. Upland kale seeds were planted in 15 x 15 cm plant spacing. The variables observed were total nitrogen, available P, exchangeable K, soil organic matter, pH, cation exchange capacity, leaf number, plant height, fresh and dry weight. The data obtained were analyzed using F test followed by Duncan Multiple Range Test (DMRT) 95%. The result showed that the organic fertilizer dose had a significant effect on all of the observed variables. Optimal doses of organic fertilizer to improve soil fertility and upland kale yield was 15 - 18 ton.ha-1. The highest yield of upland kale was observed in the treatment of 21 ton.ha-1 organic fertilizer (76.5 ton.ha-1), which was increased by 176% compared to control (34.7 ton.ha-1) and by 108.8% (45.78 ton.ha-1) compared to NPK treatments. The application of 3 ton.ha-1 organic fertilizer gave better yield of upland kale than NPK fertilizer.